Seasonal dynamics of soil aggregates and associated C and N stocks in different fertilizer managements. Issue 10 (24th August 2022) - He, Xian; Chen, Jie; Li, Yan; Chen, Yanjie; Zhao, Gaokun; Ren, Ke; Hu, Mengyang; Hu, Binbin; Chen, Yi; Xu, Zhaoli; Jin, Yan; Zhu, Yanmei; et al.
ABSTRACT: Soil aggregates and associated carbon (C) and nitrogen (N) stocks are important for soil organic matter (SOM) consequences and quality. The study is meant to understand the mechanisms of how fertilization management affects Cand Nstocks. Tobacco monocropping systems with four fertilizer treatments (0, 75, and 112kg Nha −1, and 60kg Nha −1 + manure) were established in 1998. After 19 years, crop monocrop and fertilization management redetermined soil aggregates and related indicators. The results showed the large aggregates proportion (LMP) and small macroaggregates proportion (SMP) varied inversely with changing season. The LMP gradually rose after the implementation of tillage while microaggregates gradually declined. By manure fertilizer, LMP and SMP were significantly higher than those in inorganic fertilizer treatments, while microaggregates proportion (MIP) and silt and clay proportion (SCP) were lower than in inorganic fertilizer treatments. Soil water-stable aggregate and their associated soil organic stocks are changed with growing season, and tillage practices would have potentially affected these indicators, while the proportion and soil organic stocks more quickly recovered in large aggregates by manure application. Therefore, the proper application of manure combined with chemical fertilizer would maintain soil quality in tobacco cultivation.